Fishing season in Mumbai - Mumbai Archive Project Team (Jio Institute, 2024)
The main fishing season in Mumbai begins after the monsoon rains, usually in August, when the seas are calmer and safer for fishing. The peak fishing season runs from September to April, during which the weather is favourable, and fish populations are abundant due to the nutrients that the monsoon washes into the sea.